From Laptops to Toasters: Designing and Repairing Modern Childhood Imaginaries - Ames, Morgan G.; Rosner, Daniela K. (AoIR Selected Papers of Internet Research, 2013)
We introduce two case studies that illuminate a particular way of conceptualizing childhood and technology: the One Laptop Per Child project and the East Bay Fixit Clinic. Both cases borrow narratives of childhood from contemporary American culture and the perceived potential of technology from computer cultures. The resulting narrative is also grounded in the personal childhood experiences of those involved in the communities, and their desire to provide the same kinds of experiences to children today. We highlight some of the dimensions of this narrative as well as some of its limitations in appealing to, and re-creating, a particular kind of child that resembles the (technically-inclined and often male) organizers themselves.